The COSPAR international space weather action teams (ISWAT) initiative: a driving force for the COSPAR space weather roadmap - Maria M. Kuznetsova; Mario M. Bisi; Hermann J. Opgenoorth; Martin A. Reiss; M. Leila Mays; Lucilla Alfonsi; C. Nick Arge; David Barnes; Anna Belehaki; Thomas E. Berger; Amanda Brecht; Sean Bruinsma; et al. (Advances in Space Research, 2026)

Reliable identification of flood-borne deposits in speleothems using magnetic microscopy - Samuel L. Piascik; Roger R. Fu; Nicolás M. Stríkis; Ricardo I.F. Trindade; Julio Cauhy Rodrigues; Francisco W. Cruz; Gelson F. Souza-Junior; Andrea Borsato; Vitor Azevedo; Plinio Jaqueto; Isabel Tamara Pedron; Perri Thaler; et al. (Quaternary Science Reviews, 2025)

Gossypiboma-derived lethal sarcoma in a dog - A. Rigillo; G. Giulia; M. Gambini; R. Magnoni; C. Perri; S. Remoli (Journal of Comparative Pathology, 2025)

Assessing potentially toxic elements (PTEs) content in asbestos and related groundwater: A review of the levels detected - A. Bloise; I. Fuoco; G. Vespasiano; F. Parisi; M.F. La Russa; C. Piersante; G. Perri; S. Filicetti; A. Pacella; R. De Rosa; C. Apollaro (Science of The Total Environment, 2024)

Protein Disulfide Isomerase Endoplasmic Reticulum Protein 57 (ERp57) is Protective Against ALS-Associated Mutant TDP-43 in Neuronal Cells - Sonam Parakh; Emma R. Perri; Marta Vidal; Zeinab Takalloo; Cyril J. Jagaraj; Prachi Mehta; Shu Yang; Colleen J. Thomas; Ian P. Blair; Yuning Hong; Julie D. Atkin (NeuroMolecular Medicine, 2024)
Amyotrophic Lateral Sclerosis (ALS) is a severe neurodegenerative disease affecting motor neurons. Pathological forms of Tar-DNA binding protein-43 (TDP-43), involving its mislocalisation to the cytoplasm and the formation of misfolded inclusions, are present in almost all ALS cases (97%), and ~ 50% cases of the related condition, frontotemporal dementia (FTD), highlighting its importance in neurodegeneration. Previous studies have shown that endoplasmic reticulum protein 57 (ERp57), a member of the protein disulphide isomerase (PDI) family of redox chaperones, is protective against ALS-linked mutant superoxide dismutase (SOD1) in neuronal cells and transgenic SOD1 G93A mouse models. However, it remains unclear whether ERp57 is protective against pathological TDP-43 in ALS. Here, we demonstrate that ERp57 is protective against key features of TDP-43 pathology in neuronal cells. ERp57 inhibited the mislocalisation of TDP-43 M337V from the nucleus to the cytoplasm. In addition, ERp57 inhibited the number of inclusions formed by ALS-associated variant TDP-43 M337V and reduced the size of these inclusions. ERp57 was also protective against ER stress and induction of apoptosis. Furthermore, ERp57 modulated the steady-state expression levels of TDP-43. This study therefore demonstrates a novel mechanism of action of ERp57 in ALS. It also implies that ERp57 may have potential as a novel therapeutic target to prevent the TDP-43 pathology associated with neurodegeneration.

CME propagation through the heliosphere: Status and future of observations and model development - Manuela Temmer; Camilla Scolini; Ian G. Richardson; Stephan G. Heinemann; Evangelos Paouris; Angelos Vourlidas; Mario M. Bisi; N. Al-Haddad; T. Amerstorfer; L. Barnard; D. Burešová; S.J. Hofmeister; et al. (Advances in Space Research, 2023)

Increased uterine androgen receptor protein abundance results in implantation and mitochondrial defects in pregnant rats with hyperandrogenism and insulin resistance - Yuehui Zhang; Min Hu; Fan Yang; Yizhuo Zhang; Shuting Ma; Dongqi Zhang; Xu Wang; Amanda Nancy Sferruzzi-Perri; Xiaoke Wu; Mats Brännström; Linus R. Shao; Håkan Billig (Journal of Molecular Medicine, 2021)
In this study, we show that during normal rat pregnancy, there is a gestational stage-dependent decrease in androgen receptor (AR) abundance in the gravid uterus and that this is correlated with the differential expression of endometrial receptivity and decidualization genes during early and mid-gestation. In contrast, exposure to 5α-dihydrotestosterone (DHT) and insulin (INS) or DHT alone significantly increased AR protein levels in the uterus in association with the aberrant expression of endometrial receptivity and decidualization genes, as well as disrupted implantation. Next, we assessed the functional relevance of the androgen-AR axis in the uterus for reproductive outcomes by treating normal pregnant rats and pregnant rats exposed to DHT and INS with the anti-androgen flutamide. We found that AR blockage using flutamide largely attenuated the DHT and INS-induced maternal endocrine, metabolic, and fertility impairments in pregnant rats in association with suppressed induction of uterine AR protein abundance and androgen-regulated response protein and normalized expression of several endometrial receptivity and decidualization genes. Further, blockade of AR normalized the expression of the mitochondrial biogenesis marker Nrf1 and the mitochondrial functional proteins Complexes I and II, VDAC, and PHB1. However, flutamide treatment did not rescue the compromised mitochondrial structure resulting from co-exposure to DHT and INS. These results demonstrate that functional AR protein is an important factor for gravid uterine function. Impairments in the uterine androgen-AR axis are accompanied by decreased endometrial receptivity, decidualization, and mitochondrial dysfunction, which might contribute to abnormal implantation in pregnant PCOS patients with compromised pregnancy outcomes and subfertility. Key messages The proper regulation of uterine androgen receptor (AR) contributes to a normal pregnancy process, whereas the aberrant regulation of uterine AR might be linked to polycystic ovary syndrome (PCOS)-induced pregnancy-related complications. In the current study, we found that during normal rat pregnancy there is a stage-dependent decrease in AR abundance in the gravid uterus and that this is correlated with the differential expression of the endometrial receptivity and decidualization genes Spp1 , Prl , Igfbp1 , and Hbegf . Pregnant rats exposed to 5α-dihydrotestosterone (DHT) and insulin (INS) or to DHT alone show elevated uterine AR protein abundance and implantation failure related to the aberrant expression of genes involved in endometrial receptivity and decidualization in early to mid-gestation. Treatment with the anti-androgen flutamide, starting from pre-implantation, effectively prevents DHT + INS-induced defects in endometrial receptivity and decidualization gene expression, restores uterine mitochondrial homeostasis, and increases the pregnancy rate and the numbers of viable fetuses. This study adds to our understanding of the mechanisms underlying poor pregnancy outcomes in PCOS patients and the possible therapeutic use of anti-androgens, including flutamide, after spontaneous conception.

Correction to: the Cysteine (Cys) Residues Cys-6 and Cys-111 in Mutant Superoxide Dismutase 1 (SOD1) A4V Are Required for Induction of Endoplasmic Reticulum Stress in Amyotrophic Lateral Sclerosis - Emma R. Perri; Sonam Parakh; Marta Vidal; Prachi Mehta; Yi Ma; Adam K. Walker; Julie D. Atkin (Journal of Molecular Neuroscience, 2020)

The Cysteine (Cys) Residues Cys-6 and Cys-111 in Mutant Superoxide Dismutase 1 (SOD1) A4V Are Required for Induction of Endoplasmic Reticulum Stress in Amyotrophic Lateral Sclerosis - Emma R. Perri; Sonam Parakh; Marta Vidal; Prachi Mehta; Yi Ma; Adam K. Walker; Julie D. Atkin (Journal of Molecular Neuroscience, 2020)

Females are more proactive, males are more reactive: neural basis of the gender-related speed/accuracy trade-off in visuo-motor tasks - V. Bianco; M. Berchicci; F. Quinzi; R. L. Perri; D. Spinelli; F. Di Russo (Brain Structure and Function, 2020)

Modality-specific sensory readiness for upcoming events revealed by slow cortical potentials - V. Bianco; R. L. Perri; M. Berchicci; F. Quinzi; D. Spinelli; F. Di Russo (Brain Structure and Function, 2020)

Heparin and penicillamine–hypotaurine–epinephrine (PHE) solution during bovine in vitro fertilization procedures impair the quality of spermatozoa but improve normal oocyte fecundation and early embryonic development - F. S. Gonçalves; L. S. S. Barretto; R. P. Arruda; S. H. V. Perri; G. Z. Mingoti (In Vitro Cellular & Developmental Biology - Animal, 2014)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)